Clinical significance of isolated abnormal intestinal findings in magnetic resonance enterography in patients with suspected small bowel disease - ATUĞ, ÖZLEN; TOLU BÜLTE, TUĞBA; ÖZEN ALAHDAB, YEŞİM (SPRINGER, 2020)
Purpose Magnetic resonance imaging (MRE) is a well-established adjunct diagnostic tool for the diagnosis of Crohn's Disease (CD), as ileocolonoscopy can sometimes be falsely reassuring when CD skips distal terminal ileum. We aimed to determine the frequency and clinical significance of isolated abnormal small bowel findings in MRE with normal ileal view in ileoscopy. Methods We retrospectively reviewed findings from 1611 MRE studies that were conducted between 2012 and 2018 to detect patients bearing abnormal intestinal findings and having full ileocolonoscopy. After exclusion of normal or repetitive MRE scans and previously known CD, 147 patients with abnormal MRE detected. MRE scans were categorized as suspicious of CD and non-specific findings. Results Out of 147 patients with abnormal MRE, 122 (83%) had terminal ileum involvement in MRE consistent with ileoscopy findings. Twenty-five (17%) patients were found to have solitarily abnormal intestinal findings in MRE with normal ileoscopy. Only 3 (12%) were diagnosed with CD initially, and all had MRE findings suspicious of CD. The remainder 40% (n = 10) were diagnosed with non-Crohn's small bowel disease after further investigation, while in the other 48% (n = 12) abnormal MRE findings could not be explained with any organic disease in the follow-up. Conclusion The present study demonstrated that only a small portion of patients with isolated abnormal intestinal findings in MRE is CD, and more than that are non-crohn's small bowel diseases. These findings, even if they carry the suspicion of CD, do not transform to CD in the long-term follow-up.
Keywords: Magnetic resonance enterography; Crohn's disease; Small bowel disease; Ileocolonoscpy; MR ENTEROGRAPHY; CT ENTEROGRAPHY; CROHNS-DISEASE; TERMINAL ILEITIS; DIAGNOSTIC-VALUE; FOLLOW-THROUGH; ILEUM